2011
DOI: 10.1063/1.3658258
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and nonlinear current–voltage characteristics of rare–earth doped CaCu3Ti4O12 ceramics

Abstract: were prepared by the traditional solid-state reaction method in order to investigate the effect of RE oxide dopants on the electrical properties as a varistor. The phase identification and morphology of the ceramics were investigated by x-ray diffraction (XRD) and scanning electron microscope (SEM), respectively. A high voltage measuring unit and precision impedance analyzer were used to determine the nonohmic (J-E) behaviors and measure the dielectric properties and impedance spectroscopy of the ceramics, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(30 citation statements)
references
References 21 publications
3
26
1
Order By: Relevance
“…The decrease in e 0 is associated with the decrease in the grain size. This result observed in Sm-doped CCTO ceramics is similar to those observed in literature for other Ln-doped CCTO ceramics [18][19][20][21][22][23][24][25][26]. This observation can be well ascribed based on the internal barrier layer capacitor (IBLC) model [28],…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The decrease in e 0 is associated with the decrease in the grain size. This result observed in Sm-doped CCTO ceramics is similar to those observed in literature for other Ln-doped CCTO ceramics [18][19][20][21][22][23][24][25][26]. This observation can be well ascribed based on the internal barrier layer capacitor (IBLC) model [28],…”
Section: Resultssupporting
confidence: 92%
“…The decrease in grain size of Ca 1À3x/2 Sm x Cu 3 Ti 4 O 12 ceramics is therefore due to a reduced GB mobility (or GB diffusion coefficient). It was also found that substitutions of La 3+ , Gd 3+ , Nd 3+ , and Eu 3+ for Ca 2+ in CCTO ceramics can cause a large decrease in the mean grain size [18,20,22,23,26]. The large decrease in grain size of Ca 1À3x/ 2 Sm x Cu 3 Ti 4 O 12 ceramics may be related to the solute drag mechanism, which is an important approach for reducing the GB mobility [29].…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Ceramic composite, CaCu 3 Ti 4 O 12 (CCTO) is one of the most interesting and widely investigated electroceramic materials . This is because it can exhibit a variety important properties which are required for the development of microelectronics.…”
Section: Introductionmentioning
confidence: 99%